Costa Rica : 2021 Article IV Consultation and Request for an Extended Arrangement Under the Extended Fund Facility-Press Release; Staff Report; and Statement by the Executive Director for Costa Rica. (IMF Staff Country Reports; Country Report ;, 2021)
Costa Rica has been hit hard by the COVID-19 pandemic, notwithstanding the authorities' proactive policy response and the country's well-established universal healthcare system. The socio-economic impact has been significant, exacerbating an already fragile outlook and pre-existing imbalances, with a significant toll on economic activity and unemployment-especially among women and the young. The shock has further weakened the country's fiscal position, undermining the expected yields from the ambitious fiscal reform launched in late 2018, and generated a large financing gap. Financial support through the Fund's Rapid Financing Instrument (RFI) in 2020 provided temporary relief to respond to the pandemic, including by catalyzing financial assistance from other official partners, but financing needs remain sizable over the medium term.